2011
DOI: 10.1097/gim.0b013e318226fbf2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted polymerase chain reaction-based enrichment and next generation sequencing for diagnostic testing of congenital disorders of glycosylation

Abstract: Purpose Congenital disorders of glycosylation (CDG) are a heterogeneous group of disorders caused by deficient glycosylation, primarily affecting the N-linked pathway. It is estimated that over 40% of CDG patients lack a confirmatory molecular diagnosis. The purpose of this study was to improve molecular diagnosis for CDG by developing and validating a next generation sequencing (NGS) panel for comprehensive mutation detection in 24 genes known to cause CDG. Methods NGS validation was performed on 12 positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 58 publications
2
58
1
2
Order By: Relevance
“…In such cases, MPS-based target gene analysis has been proven to be an efficient and cost-effective approach. 11,24,25 This study demonstrated that 65% (11/17) of the patients with no previous molecular diagnosis of GSD did indeed carry mutations in one of the GSD-related genes, thereby confirming the presumptive clinical diagnosis ( Table 1). Of course, the detection rate is highly dependent on an accurate clinical evaluation.…”
Section: Clinical Utility Of Mps-based Analysis Of Gsd Genesmentioning
confidence: 51%
See 2 more Smart Citations
“…In such cases, MPS-based target gene analysis has been proven to be an efficient and cost-effective approach. 11,24,25 This study demonstrated that 65% (11/17) of the patients with no previous molecular diagnosis of GSD did indeed carry mutations in one of the GSD-related genes, thereby confirming the presumptive clinical diagnosis ( Table 1). Of course, the detection rate is highly dependent on an accurate clinical evaluation.…”
Section: Clinical Utility Of Mps-based Analysis Of Gsd Genesmentioning
confidence: 51%
“…Currently, the reported MPSbased analysis of target genes relies on multiplex PCR enrichment of the coding sequences, requiring routine confirmation with additional Sanger sequencing for genes harboring low-or no-coverage exons. 11,[21][22][23] The MPS-based sequence analysis of the genes involved in glycogen metabolism presented here relies on in-solution probe hybridization for the capture of target sequences under one uniform condition, followed by MPS with deep coverage. This strategy provides an average base-by-base coverage of >600X in all target regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This very cost-effective technology is particularly appropriate for screening for mutations in disorders with highly heterogeneous genetic backgrounds, such as GSD, congenital disorder of glycosylation, lysosomal disorders, and mitochondrial disorders [5][6][7][8] In addition, its ability to detect mutations in large genes and to identify copy number variations is very advantageous. The implementation of massive parallel sequencing has begun to revolutionize the field of genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…1e9 Two widely used enrichment strategies for targeted sequencing are hybridization-capture, in which oligonucleotide baits complementary to the regions of interest are hybridized with fragmented genomic DNA, 3 and PCR, in which a pool of primers is used to generate target-specific amplicons. 4,10 Both of these approaches work well on DNA purified from formalin-fixed, paraffin-embedded (FFPE) tumor tissue, and they require only small amounts of input DNA (10 to 100 ng).…”
mentioning
confidence: 99%